Great expectations: the effect of democratic ideals on political trust in European democracies. Issue 2 (3rd April 2017) - Hooghe, Marc; Marien, Sofie; Oser, Jennifer
ABSTRACT: While in the older literature, low levels of political trust were routinely interpreted as a lack of support for democracy, more recently authors have claimed that the value pattern of critical citizens is a hallmark for a mature and stable democratic system. In this paper we assess the empirical validity of this claim, by relying on the relative deprivation literature highlighting the relation between expectation and frustration. The 2012 wave of the European Social Survey included an extensive battery measuring democratic ideals, and using latent class analysis we identify a group with high ideals on how a democracy should function. Multilevel regression analysis shows that strong democratic ideals are associated with lower levels of political trust, and most strongly so in countries with low quality of government. We close with observations on how rising democratic ideals could be a cause for the occurrence of a new group of 'critical citizens'.